Penguatan Branding dan Pemanfaatan Teknologi Digital untuk Meningkatkan Nilai Jual Produk Cencaluk di Desa Kelapapati Laut, Bengkalis - Finanta Okmayura; Khusnul Fikri; Brian Agung Cahyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This Community Service Program aimed to increase the competitiveness of cencaluk products as a traditional food typical of Bengkalis through strengthening branding and utilizing digital technology. Cencaluk is a fermented shrimp product that has been passed down through generations and has high cultural value and economic potential. The partner for this activity was the Joint Business Fishermen Group of Kelapapati Laut Village, Bengkalis, which is one of the cencaluk processing community groups in the region. This activity focused on two aspects: training in packaging design and the creation of a distinctive logo/label to strengthen product identity and increase sales value, and training in website and social media management to expand market reach through digital promotion. Implementation methods included counseling, demonstrations, and intensive mentoring. The results of the activity show that partners were able to produce more attractive packaging and logo designs, and had skills in managing digital media as a promotional tool. In addition, understanding of the importance of branding and digital marketing has increased, resulting in more effective marketing strategies. Thus, this program contributed to increase the capacity of partners in developing cencaluk as a superior regional product with high competitiveness.